The molecular mechanisms underlying neutrophil infiltration in vessel co-opting colorectal cancer liver metastases - Rada, Miran; Hassan, Nour; Lazaris, Anthoula; Metrakos, Peter (Frontiers in Oncology, 2022)
Colorectal cancer liver metastases (CRCLMs) have two major histopathological growth patterns (HGPs): desmoplastic (DHGP) and replacement (RHGP). The DHGP tumours derive their vasculature by angiogenesis, while the RHGP tumours use vessel co-option. Various studies have associated RHGP tumours with an unfavourable prognosis, as well as high levels of resistance to anti-angiogenic agents and chemotherapy. Recently, we reported higher numbers of neutrophils in the tumour microenvironment (TME) of vessel co-opting tumours compared to their angiogenic counterparts. However, the molecular mechanisms underlying this phenotype are unclear. Herein, we suggested a positive correlation between the expression of angiopoietin-1 (Ang1) in the hepatocytes and the presence of neutrophils in vessel co-opting tumours. Importantly, upregulation of Ang1 in the hepatocytes is associated with the presence of runt-related transcription factor-1 (RUNX1) in the neighbouring cancer cells in vitro and in vivo. Altogether, our data suggest the molecular mechanisms by which neutrophils are infiltrated in vessel co-opting CRCLM lesions. This finding may yield novel therapeutic strategies for CRCLM patients in future.